2015
DOI: 10.1159/000437149
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Weight Gain and Offspring Longitudinal Growth in Early Life

Abstract: Background: Excessive gestational weight gain (GWG) increases the risk of childhood obesity, but little is known about its association with infant growth patterns. Aim: The aim of this study was to examine the association between GWG and infant growth patterns. Methods: Pregnant women (n = 743) self-reported GWG at delivery, which we classified as inadequate, adequate or excessive based on the current guidelines. Offspring weight-for-age z-score (WAZ), length-for-age z-score (LAZ (with height-for-age (HAZ) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 54 publications
(59 reference statements)
1
16
1
Order By: Relevance
“…weekly weight gain was positively associated with HC. With regard to BMIZ, Diesel et al (2015) reported that newborns of women with inadequate GWG had lower BMIZ at birth (−0.44 z-score units) than newborns of women with adequate GWG, a difference that was considerably greater than the difference observed in our cohort (−0.17 z score units).…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…weekly weight gain was positively associated with HC. With regard to BMIZ, Diesel et al (2015) reported that newborns of women with inadequate GWG had lower BMIZ at birth (−0.44 z-score units) than newborns of women with adequate GWG, a difference that was considerably greater than the difference observed in our cohort (−0.17 z score units).…”
Section: Discussioncontrasting
confidence: 88%
“…Only a few studies have examined the relationship between GWG and other anthropometric birth outcomes such as LAZ (Dahly et al, ; Diesel et al, ), HCZ (Wander et al, ), and BMIZ (Diesel et al, ). In Ireland, birth length did not differ significantly between infants of mothers with excessive GWG and those of mothers with inadequate or healthy GWG (Dahly et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the role of gestational weight gain, Sridhar et al found that children born to mothers with EGWG were 46% more likely to be affected by overweight or obesity at age 2 to 5 years old after adjustment of maternal prepregnancy BMI, GDM, and other covariates . Other studies also showed that EGWG was a risk factor associated with childhood obesity at earlier ages from birth to 3 years old or at 9 to 14 years old, although neither GDM and/or prepregnancy BMI were adjusted in these analyses. None of these studies used group‐based trajectory method.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal intrauterine environment and exposures have been thought to play an important role in childhood obesity . Maternal obesity measured by BMI at the initiation of pregnancy and gestational weight gain during pregnancy are associated with childhood obesity . Diabetes during pregnancy increases the risk of childhood obesity .…”
Section: Introductionmentioning
confidence: 99%